The Effect of Teaching Style and Interest on Passing Learning Outcomes in Football Games - Amir Supriadi; Mesnan Mesnan (Universitas PGRI Palembang, 2023)
This research aimed to obtain empirical facts about the differences in learning outcomes of passing in football games between students who were taught using reciprocal and inclusive teaching styles. The research design was an experimental level 2 x 2 ANOVA factorial design. The sampling technique in this research used cluster sampling so that each group consisted of 10 students. The research results were (1) based on the analysis results of the variance in the appendix, at the level α = 0.05, Fh > Ft is 50.20 > 4.03. Thus, it could be concluded that there were differences in the learning outcomes of passing in football games between the inclusive and the reciprocal teaching styles; (2) the analyses results of the variance in the appendix, at level α = 0.05, Fh > Ft is 15.40 > 4.02; hence, it could be concluded that there was an interaction between teaching style and learning interest in the learning outcomes of passing in football games; (3) then proceed with the Tukey test in A2B2 and A1B2 groups, where Qh = 75 and Qt = 2.81; thus, it could be concluded that the reciprocal teaching style was better than the inclusive teaching style on passing learning outcomes in football material at a group of students with low interest in learning; (4) furthermore, proceed with the Tukey test in A1B1 and A2B1 groups, where Qh = 22.13 and Qt = 2.81; hence, it could be concluded that the inclusive teaching style was better than the reciprocal style on passing learning outcomes in football material at a group of students with high learning interest.